Hepatic Remote Ischemic Preconditioning (RIPC) Protects Heart Damages Induced by Ischemia Reperfusion Injury in Mice - Ren, Yanlong; Lin, Shujin; Liu, Wenxian; Ding, Huiguo (Frontiers in Physiology, 2021)
It has been convincingly demonstrated that remote ischemic preconditioning (RIPC) can make the myocardium resistant to subsequent ischemia/reperfusion injury (I/R) which causes severe damages by mainly generating cell death. However, the cardioprotective effects of hepatic RIPC which is the largest metabolic organ against I/R has not been fully studied. The aim of our research is whether remote liver RIPC may provide a cardioprotective effects against the I/R-induced injury. Here, we generated I/R mice model in four groups to analyze the effect. The control group is the isolated hearts with 140 min perfusion. I/R group added ischemia in 30 min following 90 min reperfusion. The third group (sham) was subjected to the same procedure as the latter group. The animals in the fourth group selected as treatment group, underwent a hepatic remote ischemic preconditioning by 3cycles of 5 min occlusion of portal triad and then followed by induction of I/R in the isolated heart. The level of myocardial infarction and the preventive effects of remote ischemic preconditioning were assessed by pathological characteristics including infarct, enzyme releases, pressure, and cardiac mechanical activity. Subjected to I/R, the hepatic remote ischemic preconditioning minimized the infarct size (17.7±4.96 vs50.06±5, p<0.001) and improved the left ventricular developed pressure (from 47.42±6.27 to 91.62±5.22 mmHg) and the mechanical activity. Release of phosphocreatine kinase-MB (73.86±1.95 vs 25.93±0.66 IUL-1) and lactate dehydrogenase (299.01±10.7 vs 152.3±16.7 IUL-1) were also decreased in the RIPC treated group. These results demonstrate the cardioprotective effects of hepatic remote preconditioning against the injury caused by ischemia/reperfusion in the isolated perfused hearts.